Simultaneous Estimation of Related Impurities of Tizanidine Hydrochloride in its Active Pharmaceutical Ingradient by Reversed-Phase Liquid Chromatography - Samel, Amit; Raman, Bhanu (Asian Journal of Chemistry, 2010)
A simple method was developed for qualitative and quantitative estimation of tizanidine hydrochloride and its five structurally related impurities using a reversed-phase liquid chromatography. This method was validated as per ICH guidelines for ‘validation for analytical procedures’ Q2B. The liquid chromatography was set up in UV detection mode at 310 nm. A separation was achieved between tizanidine and all five impurities in a gradient programming using YMC Pack Pro C18 (250 mm × 4.6 mm), 5 μ column at 1 mL/min flow rate. This method was established to be linear in a concentration range of (0.5-4.0 μg/mL) for all the components considered in this study. Limit of detection (LOD) and limit of quantification (LOQ) values were found to be (0.1-0.15 μg/mL) and (0.3-0.45 μg/mL) for tizanidine hydrochloride and its five related impurities, respectively. Recoveries of all spiked impurities in tizanidine hydrochloride were in a range of (95- 105 %). Robustness and sample solution stability studies demonstrated the ruggedness of this method. This method is simple, sensitive and provides precisely accurate results.